Tingkat Pengetahuan dan Sikap Ibu dengan Praktek Pemberian Makanan dalam Pencegahan dan Penatalaksanaan Anak Stunting - Delima Irfan; Daharnis Daharnis; Zadrian Zadrian (Jurnal Sehat Mandiri, 2024)
Stunting or stunted growth in children is still a global problem. The prevalence of stunting in Indonesia in children under 5 years of age is 22.3%. Meanwhile, in West Sumatra, the prevalence of stunting is higher than the national prevalence, namely 25.6% in 2022. Solok Regency with the highest incidence of 40.1% in 2021. This research aims to look at the relationship between knowledge, attitudes, and feeding practices in the management of stunted children. This research uses a quantitative approach with a Case-Control design. The research was conducted in Solok Regency, specifically the working area of the Sungai Lasi Community Health Center. The population of this study was mothers who had stunted children under 5 years of age (168 people), while the sample included mothers who had stunted children under 2 years of age (17 people). The sample ratio was 1:2 (stunting (17 people) and not stunting (34 people) with a total of 51 people. Sampling was done using purposive sampling. Data analysis used univariate analysis, and bivariate analysis using the Chi-square test. The results of the bivariate analysis obtained the mother's level of knowledge (p= 0.013) and the mother's attitude (p=0.035). In conclusion, there is a relationship between a mother's level of knowledge and attitude and feeding practices in managing stunting. Efforts are needed to increase mothers' knowledge and attitudes in preventing and managing stunting.